Differences Effect of Shooting Exercise and Taste Believe Yourself in Free Throw on Extraculicular Students SMA Negeri 1 Medan - Roni Fathan Hasibuan; Imran Akhmad; Sanusi Hasibuan (Journal Physical Education, Health and Recreation, 2020)
The purpose of this study was to determine the effect of rope training and wall shoots with confidence. This study uses the experimental method. Data collection techniques in this study used questionnaires and observations. Analysis technique